KAJIAN SISA HASIL USAHA KOPERASI UNIT DESA DI KABUPATEN MUARO JAMBI - Estela, Ellen; Fitri, Yanuar; Malik, Adlaida (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
This researchaims aims to (1) to find out the description of the condition of the KUD that is still active in Sungai Bahar and South Bahar Subdistricts, Muaro Jambi Regency South Bahar. (2) Knowing the effect of business volume, number of members and own capital on the acquisition of the remaining operating results in KUD in Sungai Bahar and South Bahar Districts. The object of research is KUD which is still active in conducting Annual Member Meetings and has a business unit other than marketing Fresh Fruit Bunches (FFB), savings and loans. This research was conducted from September to October 2017. The data used is secondary data obtained directly from cooperatives through books, archives related to Business Remaining for 5 years from 2012 to 2016 and from the UMKM Department and the Muaro Regency Industry and Trade Cooperative Service Jambi and other related literature. KUDs taken as samples are KUD ​​Mekar Sari, KUD Tandan Buah Segar, KUD Selikur Makmur, KUD Sumber Makmur, KUD Sri Rejeki and KUD Dwi Jaya on the consideration that the six KUDs are still active in conducting Annual Member Meetings and have other business units besides marketing FFB and savings and Loan. The results showed that (1) KUDs that were still active in Sungai Bahar Subdistrict were 5 KUDs from 11 existing KUDs and 5 KUDs that were still active in the South Bahar District of the 7 KUDs that were available. KUDs that are no longer active are caused by no longer routinely performing RATs, misappropriation of cooperative funds and declining member participation due to internal conflicts with members of the cooperative management. (2) From the results of multiple linear analysis, the business volume variable does not significantly affect the acquisition of operating results with value. probability of 0.2296 means that it is greater than the real level of 0.05, this is due to the high level of credit of members in the cooperative and not paying credit debt on time and the amount that has been determined, the variable number of members and own capital together have a real effect regarding the acquisition of operating results with a probability value of 0.0002 and 0.0003, respectively.